Research Journal of Applied Sciences, Engineering and Technology 7(16): 3342-3347, 2014 ISSN: 2040-7459; e-ISSN: 2040-7467 © Maxwell Scientific Organization, 2014 Submitted: September 28, 2013 Accepted: November 19, 2013 Published: April 25, 2014 Oscillation Criteria for Ordinary Differential Equations of Second Order Nonlinear with Alternating Coefficients Ambarka A. Salhin, Ummul Khair Salma Din, Rokiah Rozita Ahmad and Mohd Salmi Md Noorani School of Mathematical Sciences, Faculty of Science and Technology, Universiti Kebangsaan Malaysia, 43600 UKM Bangi, Selangor, Malaysia Abstract: Several new oscillation criteria are established under quite general assumptions. Our results generalize and extend some earlier results of the literature. Examples are given to illustrate the results. We employ the averaging technique to obtain sufficient conditions for oscillation in the solutions of our equation. Keywords: Averaging technique, nonlinear differential equations, oscillation criteria, Riccati substitution, second order INTRODUCTION The study of the oscillation of second order nonlinear ordinary differential equations with alternating coefficients is of special interest because of the fact that many physical systems are modeled by second-order nonlinear ordinary differential equations. For example, the so called Emden-Fowler equation arises in the study of gas dynamics and fluid mechanics. This equation appears also in the study of relativistic mechanics, nuclear physics and in the study of chemically reacting systems. The averaging techniques are used also in study of the nonlinear oscillations. This study is concerned with the oscillation of solutions of the second order nonlinear differential equation: oscillatory if it has a sequence of zero clustering at ∞ and non-oscillatory otherwise. Thus a non-oscillatory is either eventually positive or eventually negative. Equation (1) is called oscillatory if all its solutions are oscillatory and otherwise it is called non-oscillatory. Both oscillatory and non-oscillatory behavior of solutions for various classes of second order differential equations have been widely discussed in the literature, see for example; Elabbasy and Elsharabasy (1997), Grace and Lalli (1980, 1992), Grace (1990), Kiran and Rogovchenko (2001), Philos (1975), Wong (1986), Wong and Yeh (1992), Wintner (1949), Yan (1986) and Yeh (1982). There are a great number of papers addressing particular cases of Eq. (1), such as the following equations (Li, 1998; Manojlovic, 1999, 1991; Tiryakiand Ayanlar, 2004): (r (t )ψ ( x(t )) f ( x′(t )))′ + q(t ) g ( x(t )) = H (t , x′(t ), x(t )), (1) where, q and r : Continuous functions on the interval (t 0 , ∞), t 0 ≥0 r(t) : A positive function ψ and f : Continuous functions on the real line ℝ, with ψ (x) >0, ∀ x ∈ ℝ and yf (y) >0 for y ≠ 0 g : Continuously differentiable function on the real line, ℝ, except possible at 0 with xg (x) >0 and g' (x) ≥k>0 for all x ≠ 0 and k is a constant H : A continuous function on [t 0 , ∞) × ℝ2 , with H (t , y, x) ≤ p (t ) , ∀ 𝑡𝑡 ∈ [t 0 , ∞), y ∈ ℝ and x ≠ 0 g ( x) By a solution of (1), we mean a nontrivial function x (t) satisfying (1). A solution x (t) is said to be H (t ), ( r (t ) x′(t )α )′ + q(t ) g ( x(t )) = (2) H (t ), ( r (t )ψ ( x) x′(t ) )′ + q (t ) g ( x) = (3) H (t , x(t ), x′(t )), ( r (t ) x′(t ) )′ + Q(t , x) = (4) (5) H (t ). ( r (t )ψ ( x(t )) f ( x′(t )) )′ + q(t ) g ( x(t )) = An important tool in the study of oscillatory behaviour of solutions of these equations is the averaging technique which goes back as far as the classical result of Wintner (1949) which states that (2) with r (t) = 1, α = 1, g (x) = x and H (t) = 0 is oscillatory if: Corresponding Author: Ambarka A. Salhin, School of Mathematical Sciences, Faculty of Science and Technology, Universiti Kebangsaan Malaysia, 43600 UKM Bangi, Selangor, Malaysia 3342 Res. J. App. Sci. Eng. Technol., 7(16): 3342-3347, 2014 ′ t s 1 q (u ) du ds = ∞. t →∞ t ∫ ∫ t0 t0 lim w′(t ) = In this study, the comparison between our results and the previously known results are presented and some examples of the main results are illustrated. Furthermore, we expand some of the previous equations, (Baculikova, 2006; Tiryaki and Ayanlar, 2004) as well as the expansion and development of some of the previous conditions (Elabbasy et al., 2005; Graef et al., 1978; Remili, 2008). ρ (t ) [ r (t )ψ ( x(t )) f ( x′(t ))] ρ ′(t )r (t )ψ ( x(t )) f ( x′(t )) + g ( x(t )) g ( x(t )) ρ (t )r (t )ψ ( x(t )) f ( x′(t )) g ′( x(t )) x′(t )) , − g 2 ( x(t )) ρ (t ) H (t , x′(t ), x(t )) = w′(t ) − ρ (t )q (t ) + ρ ′(t ) w(t ) ρ (t ) g ( x(t )) 1 − x′(t ) g ′( x(t )) w2 (t ). ρ (t )r (t )ψ ( x(t )) f ( x′(t )) From conditions O 1 and O 3 we obtain: MAIN RESULTS w′(t ) ≤ ρ (t ) ( p (t ) − q (t ) ) + In this section, we use the Riccati technique to establish sufficient conditions for Eq. (1) to be oscillatory. ρ ′(t ) K w(t ) − w2 (t ) , ρ (t ) ρ (t )r (t )k2 M ρ ′(t ) w(t ) − w2 (t ) − w′(t ). ρ (t ) ρ (t )r (t ) ρ (t ) ( q(t ) − p (t ) ) ≤ Theorem 1: Suppose that: Integrating from t 0 to t gives following result: O 1 : g ′( x) ≥ K > 0 for a constant K and x ≠ 0, ψ ( x) ±∞ O 2 : ∫ ψ ( y ) dy < ∞ for all ε > 0 , ±ε g ( y ) O 3 : 0 < k ≤ f ( y) ≤ k 1 2 y for all constants k1 , k2 , y = x′(t ) ≠ 0 and lim t →0 f ( y) y t t M 2 ρ ′( s ) 0 t0 t ∫ ρ ( s ) ( q( s ) − p ( s ) ) − t0 2 t r ( s ) ρ ( s ) ρ ′( s ) r ( s ) ρ ( s ) ρ ′( s ) M ds ≤ w(t0 ) − w(t ) − ∫ w( s ) − ds, 4 M ρ ( s ) r( s)ρ ( s) 2 M ρ ( s) t0 2 ≤ w(t0 ) − w(t ), or, exist. t t0 ∫ ρ ( s) ( q( s) − p( s) ) − There also exists a positive function ρ ∈ C 1 [t 0 , ∞) such that ( ρ (t )r (t ) )′ ≤ 0 for all t ≥ t0 , and: 2 r ( s ) ρ ( s ) ρ ′( s ) ρ (t )r (t )ψ ( x (t )) f ( x′(t )) . ds ≤ w(t0 ) − 4 M ρ ( s) g ( x (t )) Using condition O 3 : O4: t ρ (t )r (t )ψ ( x(t )) x′(t ) r ( s ) ( ρ ′( s )) 2 ds ≤ w(t0 ) − k1 . ρ ( s) g ( x(t )) ∫ ρ (s) ( q(s) − p(s) ) − 4M t s 1 ( ρ ′(u )) 2 lim sup ∫ ∫ ρ (u )[ q (u ) − p (u )] − r (u ) du ds = ∞, t →∞ t t0 t0 4 M ρ (u ) t0 Taking a second integration from t 0 to t we have: where, t s M = ∫ ρ ( s) ( q( s) − p( s) ) ds ≤ w(t ) − w(t ) − ∫ r( s)ρ ( s) w ( s) − ρ ( s) w( s) ds, t0 K k2 . t0 t0 t (7) Then Eq. (1) is oscillatory. Proof: On the contrary we assume that Eq. (1) has a non-oscillatory solution, x(t ) . We suppose without loss of generality that x (t ) > 0 for all t ∈ [t0 , ∞) . We Since r (t ) ρ (t ) is non-increasing, then by the Bonnet’s Theorem there exists an η ∈ [t 0 , t ] such that: t − k1 ∫ ρ ( s )r ( s ) t0 define the function w(t ) as: w(t ) = r (u ) ( ρ ′(u )) 2 ρ ( s)r ( s)ψ ( x( s)) x′( s ) duds ≤ w(t0 )(t − t0 ) − k1 ∫ ds . ρ (u ) g ( x( s )) t0 ∫ ∫ ρ (u) ( q(u) − p(u) ) − 4M ρ (t )r (t )ψ ( x(t )) f ( x′(t )) g ( x(t )) η ψ ( x( s )) x′( s ) ψ ( x( s )) x′( s ) ds = ds −k1r (t0 ) ρ (t0 ) ∫ g ( x( s )) g ( x( s )) t 0 = k1r (t0 ) ρ (t0 ) x ( t0 ) ∫ x (η ) for all t ≥ t0 . ψ ( y) dy g ( y) 0, ∞ < ψ ( y) k1r (t0 ) ρ (t0 ) ∫ g ( y ) dy ε (6) Differentiating Eq. (6) and substituting Eq. (1) imply: hence, 3343 if x(t0 ) < x(η ), if x(t0 ) > x(η ), Res. J. App. Sci. Eng. Technol., 7(16): 3342-3347, 2014 t − ∞ < − k1 ∫ r ( s ) ρ ( s ) ψ ( x) x′( s ) g ( x) t0 1 t s 1 1 1 u = lim sup ∫ ∫ 1 + sin u − 3 − × 0 du t →∞ t t0 t0 2 u 4M = ∞. ds < L1 , where, ∞ L1 = k1r (t0 ) ρ (t0 ) ∫ ε ψ ( y) g ( y) By Theorem 1, this equation is oscillatory. dy . Remark 1: Theorem 1 improves and expands to the Theorem 4 of Graef et al. (1978) and to the Theorem 1 of Elabbasy et al. (2005). Equation (7) becomes: t s r (u ) ( ρ ′(u )) 2 duds ≤ w(t0 )(t − t0 ) + L1. ρ (u ) ∫ ∫ ρ (u ) ( q(u ) − p(u ) ) − 4M t0 t0 Theorem 2: Assume that O 2 holds and: (8) Dividing (8) by t and taking the upper limit as 𝑡𝑡 → ∞: lim sup t →∞ t s 1 r (u ) ( ρ ′(u )) 2 1 sup [ w(t0 )(t − t0 ) + L1 ] ρ (u ) ( q (u ) − p (u ) ) − du ds ≤ lim t →∞ t t∫0 t∫0 4 M ρ (u ) t < ∞. This contradicts the assumption O 4 , which completes the proof. O 5 : f ( y ) > L > 0; for a constant L and y ≠ 0, y there exists a positive continuously differentiable ∞ function ρ defined as in Theorem 1 and ∫𝑡𝑡 𝜌𝜌(𝑠𝑠)𝑑𝑑𝑑𝑑 = 0 ∞ Then Eq. (1) is oscillatory if: O6: t lim sup ∫ ρ ( s )ds t →∞ t0 Example 1: Consider the following equation: ′ 1 ( x′(t ))3 1 x 7 (t ) cos t sin x′(t ) π , t≥ . = + + sin t x3 (t ) 3x′(t ) + 2 ( x′(t )) + 1 2 2 x 4 (t ) + 1 t 3 t ( ) Notice that: −1 t s t0 t0 ∞. ∫ ρ (s) ∫ [ q(u ) − p(u )] du ds = Proof: On the contrary we assume that Eq. (1) has a non-oscillatory solution x (t). We suppose without loss of generality that x (t) >0 for all t ∈ (t 0 , ∞). We define the function w (t) as: t w(t ) = ρ (t ) ∫ H (t , x′(t ), x(t )) x 7 cos t sin x′ 1 1 = × 3 ≤= p (t ) , ∀x′ ∈ , x ∈ and t ≥ t0 , g ( x(t )) ( x 4 + 1)t 3 x t3 t0 r ( s )ψ ( x( s )) f ( x′( s )) for all t ≥ t . 0 ds g ( x( s )) Thus, for every t ≥ t0 we obtain: and r ( s )ψ ( x( s )) f ( x′( s )) ρ (t )r (t )ψ ( x(t )) f ( x′(t )) (9) . ds + g ( x( s )) g ( x(t )) t0 g ′( x) 3 x 2 = ≥ 3= k , ψ ( x) 1 ±∞ ∫ ψ ( y) ±ε g ( y) 3 < 3+ dy = − 1 2 y2 t = w′(t ) ρ ′(t ) ∫ ±∞ = ±ε 1 < ∞, 2ε 2 From Eq. (1) and definition function H, we have: ′ f ( x′(t )) ] [ r (t )ψ ( x(t )) = g ( x(t )) ( x′(t )) 2 f ( y) 3. < 4 , ∀y ≠ 0, lim = y →0 ( x′(t )) 2 + 1 y 1 − 2 < 0, 1 ρ ′(t ) =∈ 0 C1 [t0 , ∞ ) , ( ρ (t )r (t ) )′ = ρ (t ) =⇒ t O4: lim sup H (t , x, x′) − q (t ) g ( x(t )) ′ [ r (t )ψ ( x(t )) f ( x′(t ))] Let, t →∞ ds g ( x(t )) ≤ p (t ) − q (t ). Integrate the above inequality from t 0 to t and integrate the left hand side by parts we obtain: t s 1 r (u ) ( ρ ′(u )) 2 ρ (u ) ( q (u ) − p (u ) ) − duds ∫ ∫ t t0 t0 4 M ρ (u ) [ r (t )ψ ( x(t )) f ( x′(t ))] − B + t r (s)ψ ( x(s)) f ( x′(s)) g ′( x(s)) x′(s) ds ≤ t g ( x(t )) 3344 ∫ t0 g 2 ( x( s )) ∫ p(s) − q(s)ds, t0 Res. J. App. Sci. Eng. Technol., 7(16): 3342-3347, 2014 B= if x(t0 ) < x(η ), 0 ∞ < ψ ( y) L r ( t ) ρ ( t ) dy 0 0 ∫ ε g ( y) where, r (t0 )ψ ( x(t0 )) f ( x′(t0 )) . g ( x(t0 )) Now, multiply the last inequality by ρ (t) we obtain: if x(t0 ) > x(η ), hence, ρ (t )r (t )ψ ( x (t )) f ( x′(t )) (10) ≤ Bρ (t ) − ρ (t ) ∫ q( s ) − p( s )ds. g ( x (t )) t t t −∞ < − ∫ 0 Substituting (10) in (9) we have: ρ ( s )r ( s )ψ ( x( s )) x′( s ) g ( x( s )) t0 ds ≤ B1 , where, r ( s )ψ ( x( s )) f ( x′( s )) ds ≤ ρ (t ) B − ρ (t ) ∫ (q ( s ) − p ( s ))ds. g ( x( s )) t0 t0 t t w′(t ) − ρ ′(t ) ∫ B1 = ρ (t0 )r (t0 ) x ( t0 ) ∫η ψ ( y) g ( y) x( ) dy. Integrate from t 0 to t we have: Consequently: t s t t s t0 t0 t0 t0 t0 ∫ ρ (s)∫ (q(u ) − p(u ))du ds ≤ w(t0 ) − w(t ) + B ∫ ρ (s)ds + ∫ ρ ′(s)∫ r (u )ψ ( x(u )) f ( x′(u )) du ds g ( x(u )) t s t t0 t0 t0 ∫ ρ (s)∫ (q(u ) − p(u ))du ds ≤ M + B ∫ ρ (s)ds, (11) Now evaluate using integration by parts: where, r (u )ψ ( x(u )) f ( x′(u )) r (u )ψ ( x(u )) f ( x′(u )) du ds = ρ ( s ) ∫ du ∫ ρ ′(s)t∫ g ( x ( u )) g ( x(u )) t0 t 0 0 t s t −∫ s ρ ( s )r ( s )ψ ( x( s )) f ( x′( s )) g ( x( s )) t0 0 t M = w (t 0 ) + LB 1 t0 Then, ds t ∫ ρ ( s )ds t0 r ( s )ψ ( x( s )) f ( x′( s )) ρ ( s )r ( s )ψ ( x( s )) f ( x′( s )) ρ (t ) ∫ ds − ∫ ds g ( x ( s )) g ( x( s )) t0 t0 t t t = w(t ) − ∫ ρ ( s )r ( s )ψ ( x( s )) f ( x′( s )) g ( x( s )) t0 Substituting (12) in (11) we obtain: t t0 s t0 t t t0 t0 ∫ ρ (s)∫ (q(u ) − p(u ))du ds ≤ w(t ) − w(t ) + B ∫ ρ (s)ds + w(t ) − ∫ ρ ( s )r ( s )ψ ( x( s )) f ( x′( s )) 0 t t ≤ w(t0 ) + B ∫ ρ ( s )ds − ∫ t0 t0 g ( x( s )) ρ ( s )r ( s )ψ ( x( s )) f ( x′( s )) g ( x( s )) s t0 t t t t0 t0 t0 ( g ( x( s )) + B. ∫ ρ (s)ds ) ( x 3 (t ) ( x′(t ))2 = sin t , t ≥ t0 1 . 2 ′(t ))2 + 1 x ( x (t ) + 1 2 ) H (t , x′(t ), x(t )) ( x′(t )) 2 1 = x 3 (t )sin t × g ( x(t )) ( x′(t )) 2 + 1 x(t ) 1 + x 2 (t ) ds. ( ±∞ ψ ( y) ±∞ ± ± η = ρ (t0 )r (t0 ) y dy ∫ = dy ∫ε= g ( y) ε (1 + y ) 2 2 ψ ( x( s )) x′( s ) ds = ds − ρ (t0 )r (t0 ) ∫ g ( x( s )) t0 x ( t0 ) ∫η x( ) ψ ( y) g ( y) ) 2 ≤ sin = = t p (t ), ∀x′ ∈ , x ∈ and t ≥ t 0 1, ( ρ (t )r (t ) )′ ≤ 0 then by Bonnet’s Theorem g ( x( s )) t0 ′ 2 1 2 ′ 3 = + t x(t ) 1 + x 2 (t ) x t x t ( ) ( ) t ds. ρ ( s )r ( s )ψ ( x( s )) x′( s ) 0 ρ ( s )r ( s )ψ ( x( s )) x′( s ) ds there exist a η ∈ [t0 , t ] such that: −∫ t0 M t Taking the upper limit as 𝑡𝑡 → ∞ which contradicts the assumption O 6 . This completes the proof. (13) Since s Notice that: ∫ ρ (s)∫ (q(u ) − p(u ))du ds ≤ w(t ) + B ∫ ρ (s)ds − L ∫ t0 Example 2: Consider the nonlinear differential equation: From condition O 5 we get: t t ∫ ρ (s)∫ (q(u ) − p(u ))du ds ≤ t0 (12) ds. −1 Let, r (t ) = dy 3345 1 , ρ (t ) 1 = t 1 ( 4 1+ ε 2 ) 2 < ∞. Res. J. App. Sci. Eng. Technol., 7(16): 3342-3347, 2014 We have: REFERENCES − ( ρ (t )r (t ) )′ = 1 <0 t2 Baculikova, B., 2006. Oscillation criteria for second order nonlinear differential equations. Brno. Archivum Mathematicum. Tomus., 42: 141-149. and Elabbasy, E.M. and M.A. Elsharabasy, 1997. Oscillation properties for second order nonlinear ∞ ∞ differential equations. Kyungpook Math. J., 37: ∫t ρ (s)ds = ∫1 ds = ∞, 211-220. Elabbasy, E.M., S.T. Hassan and H.S. Saker, 2005. Oscillation of second-order nonlinear differential and equations with damping term. Electron. J. Differ. Equ., 76: 1-13. lim sup ∫ ρ ( s )ds ∫ ρ ( s ) ∫ [ q (u ) − p (= u )] du ds lim sup ∫ ds ∫ ∫ u − sin u du ds Grace, S.R., 1990. Oscillation criteria for second order differential equations with damping. J. Aust. Math. 1 t5 1 1 1 Soc. A, 49: 43-54. = lim sup + sin t − t − t cos1 − + sin1 − − cos1 t →∞ t − 1 20 4 20 4 Grace, S.R. and B.S. Lalli, 1980. Oscillation theorems = ∞. for certain second order perturbed nonlinear differential equations. J. Math. Anal. Appl., 77: Hence, this equation is oscillatory by Theorem 2. 205-214. Grace, S.R. and B.S. Lalli, 1992. Oscillation theorems Remark 2: It is straightforward to check that the for second order superlinear differential equations conclusion of the Theorem 2 is still true if: with damping. J. Aust. Math. Soc. A, 53: ∞ 156-165. 0 < ∫ ρ ( s )ds < ∞, Graef, J.R., S.M. Rankin and P.W. Spikes, 1978. t Oscillation theorems for perturbed nonlinear differential equations. J. Math. Anal. Appl., 65: t s 375-390. ∞. lim sup ∫ ρ ( s ) ∫ [ q (u ) − p (u ) ] du ds = t →∞ Kiran, M. and V.Y. Rogovchenko, 2001. On oscillation t t of nonlinear second order differential equation with damping term. Appl. Math. Comput., pp: Remark 3: If 𝑟𝑟(𝑡𝑡) = 1, 𝜓𝜓 �𝑥𝑥 (𝑡𝑡)� = 1, 𝑓𝑓 �𝑥𝑥 ′ (𝑡𝑡)� = 117-192. ′ ′ 𝑥𝑥 , 𝑔𝑔 �𝑥𝑥 (𝑡𝑡)� = 𝑥𝑥 and 𝐻𝐻 �𝑡𝑡, 𝑥𝑥 (𝑡𝑡), 𝑥𝑥 (𝑡𝑡)� = 0 then Li, W.T., 1998. Oscillation of certain second order Theorem 2 reduces to Wintner‘s theorem (1949). nonlinear differential equations. J. Math. Anal., 194: 1-14. Remark 4: Remili (2008) has established some Manojlovic, J.V., 1991. Oscillation theorems for . oscillation results for Eq. (1) with ′ ′ = ψ ( x) 1,= f ( x (t )) x nonlinear second order differential equations. These results require that: Math. Subject Classification, 1: 1-14. Manojlovic, J.V., 1999. Oscillation theorems for a (t ) ≤ a1 nonlinear second order differential equations. Acta Sci. Math., 65: 515-527. and Philos, C.G., 1975. Oscillation theorems for second t order nonlinear differential equations. Bull. Inst. lim inf ∫ Z ( s )ds > −λ (λ > 0) for all large T ; Math. Acad. Sinica, 3: 283-309. t →∞ T Remili, M., 2008. Oscillation theorem for perturbed nonlinear differential equations. Int. Math. Forum, = Z ( s) R( s) [ q( s) − p( s)] , 11: 513-524. Tiryaki, A. and B. Ayanlar, 2004. Oscillation theorems for certain nonlinear differential equations of which are not required in Theorem 2. second order. Comput. Math. Appl., 47: 149-159. Wintner, A., 1949. A criterion of oscillatory stability. ACKNOWLEDGMENT Quart. Appl. Math., 7: 115-117. Wong, J.S.W., 1986. An oscillation criterion for second This research has been completed with the support order nonlinear differential equations. Proc. Amer. of these grants: UKM-DLP-2011-049 and FRGS/ 1/2012/SG04/UKM/01/1. Math. Soc., 98: 109-112. 0 −1 t t s t −1 t s 1 1 1 3 t →∞ t0 t0 t →∞ t0 0 0 0 3346 Res. J. App. Sci. Eng. Technol., 7(16): 3342-3347, 2014 Wong, F.H. and C.C. Yeh, 1992. Oscillation criteria for second order superlinear differential equations. Math. Japonica, 37: 573-584. Yan, J., 1986. Oscillation theorems for second order linear differential equations with damping. Proc. Amer. Math. Soc., 98: 276-282. Yeh, C.C., 1982. Oscillation theorems for nonlinear second order differential equations with damping term. Proc. Amer. Math. Soc., 84: 397-402. 3347